2014
DOI: 10.5123/s1679-49742014000100013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da completitude, da consistência e da duplicidade de registros de violências do Sinan em Recife, Pernambuco, 2009-2012

Abstract: Métodos: foi realizado estudo descritivo; a qualidade da base de dados do Sinan foi avaliada quanto à completitude e consistência de 35 variáveis e não duplicidade de registros; aplicou-se o teste do qui-quadrado para tendência linear (p<0,05) para avaliação da completitude e consistência. Resultados: no período 2009-2012, houve aumento de 283,9% no número de notificações, as médias percentuais de completitude, de consistência e de duplicidade foram, respectivamente, de 70,3%, 98,5% e 0,2%; houve redução de 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
29
1
41

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(75 citation statements)
references
References 11 publications
4
29
1
41
Order By: Relevance
“…23 The variables Municipality, Neighborhood, Address and Place of occurrence of the section Data of the Occurrence had 'Bad' completeness. Similar results have been found in other studies that evaluated the VIVA, 12,15 as well as analyses of data on deaths from external causes. 21 The home has been pointed out as the main place where violent episodes occur at all ages, followed by public streets.…”
supporting
confidence: 78%
See 4 more Smart Citations
“…23 The variables Municipality, Neighborhood, Address and Place of occurrence of the section Data of the Occurrence had 'Bad' completeness. Similar results have been found in other studies that evaluated the VIVA, 12,15 as well as analyses of data on deaths from external causes. 21 The home has been pointed out as the main place where violent episodes occur at all ages, followed by public streets.…”
supporting
confidence: 78%
“…In this case, it is inferred that the flawed filling resulted from lack of knowledge of the professionals about the protection network. 12 Referrals were made to the Protection and Assistance Instances (40.0%), Reference Centers (25.8%) and Police stations (18.9%), with a small number of referrals carried out in order to maintain and ensure the continuity of care for these victims, as revealed in the study conducted in Feira de Santana (BA). 24 The variable of the Outcome of the case had 'Bad' completeness, corroborating the MOH publication that showed that 24.8% of the records had no information on the outcome of the cases.…”
mentioning
confidence: 99%
See 3 more Smart Citations